2012
DOI: 10.1051/epjconf/20123902001
|View full text |Cite
|
Sign up to set email alerts
|

Tidal disruption of stars by supermassive black holes: The X-ray view

Abstract: Abstract. The tidal disruption of stars by supermassive black holes produces luminous soft X-ray accretion flares in otherwise inactive galaxies. First events have been discovered in X-rays with the ROSAT observatory, and have more recently been detected with XMM-Newton, Chandra and Swift, and at other wavelengths. In X-rays, they typically appear as very soft, exceptionally luminous outbursts of radiation, which decline consistent with L ∝ t −5/3 on the timescale of months to years. They reach total amplitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…Good candidates have been found for such events, both in the optical/UV (Gezari et al 2008(Gezari et al , 2009van Velzen et al 2011;Chornock et al 2014) and in X-rays (Brandt, Pounds & Fink 1995;Grupe et al 1995;Bade, Komossa & Dahlem 1996;Halpern, Gezari & Komossa 2004;Komossa et al 2004;Komossa 2012). Could our slow-blue transients be examples of TDEs?…”
Section: Tidal Disruption Eventsmentioning
confidence: 99%
“…Good candidates have been found for such events, both in the optical/UV (Gezari et al 2008(Gezari et al , 2009van Velzen et al 2011;Chornock et al 2014) and in X-rays (Brandt, Pounds & Fink 1995;Grupe et al 1995;Bade, Komossa & Dahlem 1996;Halpern, Gezari & Komossa 2004;Komossa et al 2004;Komossa 2012). Could our slow-blue transients be examples of TDEs?…”
Section: Tidal Disruption Eventsmentioning
confidence: 99%
“…Some of TDEs have also been detected in the optical and UV bands (e.g., Gezari et al 2006Gezari et al , 2008Gezari et al , 2012Arcavi et al 2014;Holoien et al 2014;van Velzen et al 2011). Since the first detection of a TDE, which occurred in NGC 5905 (Bade et al 1996), a few tens of X-ray TDEs have been identified (Komossa 2012). The identifications of TDEs were mainly based on their variability characteristics, such as a large amplitude and the unique decline law of the light curve (e.g., Komossa & Bade 1999), which are supported by both analytic solutions (Rees 1988;Phinney 1989) and numerical simulations (e.g., Evans & Kochanek 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors [7], [8], [9], [10] interpreted this emission as coming from the total tidal disruption of a star orbiting around the central massive black hole (∼ 3 × 10 5 M [11]) of the galaxy, even if IC 3599 is a low-luminosity active galactic nucleus (AGN). Indeed in AGNs it is difficult to distinguish between variability coming from the galaxy itself and variability induced by the disruption of a star, even if in AGNs the presence of a pre-existent accretion disk enhances the probability to have tidal disruption events [12], [13].…”
Section: The Case Of Ic 3599mentioning
confidence: 99%